Use of untargeted metabolomics for assessing soil quality and microbial function. (April 2020) - Withers, Emma; Hill, Paul W.; Chadwick, David R.; Jones, Davey L.
Abstract: Soils support a wide range of ecosystem services that underpin Earth system functioning. It is therefore essential that we have robust approaches to evaluate how anthropogenic perturbation affects soil quality and the delivery of these services. Metabolomics, the large-scale study of low molecular weight organic compounds in soil, offers one potential approach to characterise soils and evaluate the metabolic status of the soil biological community. The aims of the present study were to 1) characterise the soil metabolome across a contrasting range of soil types, 2) understand the relationships between common chemical and physical soil quality indicators and its metabolome, and 3) evaluate the discriminatory power of soil metabolomics and its potential use as a soil quality indicator. Nine different topsoils with 5 replications were collected along an altitudinal primary productivity gradient encompassing a wide range of soil types and land uses. Metabolites were extracted from soil using 3:3:2 (v/v/v) acetonitrile:isopropanol:water and individual compounds identified using a gas chromatography-mass spectrometry (GC-MS) platform. Overall, 405 individual compounds were detected, of which 146 were positively identified, including sugars, amino acids, organic acids, nucleobases, sugar alcohols, lipids and a range of secondary metabolites. The concentration and profile of metabolites was found to vary greatly between the soil types. Further, the soils' metabolomic fingerprints correlated to a number of environmental factors, including pH, land-use, moisture and salinity. We also tentatively attributed soil-specific metabolites to potential functional pathways, although complementary proteomic, genomic and transcriptomic approaches would be needed to provide definitive supporting evidence. In conclusion, soil metabolomics offers the potential to reveal the complex molecular networks and metabolic pathways operating in the soil microbial community and a means of evaluating soil function. Further work is now required to benchmark soil metabolomes under a wide range of management regimes so that they can be used for the quantitative assessment of soil quality. Graphical abstract: Image 1 Highlights: Soil metabolites were extracted using acetonitrile, isopropanol and water. Metabolites with contrasting chemical properties were detected using GC-MS. Soils could be categorized into 4 distinct groups based on metabolite profiles. Soil metabolomic fingerprints correlated to several environmental factors. Potential functional pathways were indicated for exploration.